Analysis Of PTMA Employees' Understanding In Central Kalimantan Of The Existence Of Ortom Muhammadiyah - Kholisotin, Lilik; Kartini, Nurul Hikmah; Mayaputri, Velmi (LPPM Universitas PGRI Sumatera Barat, 2024)
Cadre formation is very important in a charity business, because these cadres will become the successors, pioneers and successors of Muhammadiyah in the future. The Muhammadiyah Autonomous Organization (Ortom) is an organization or body formed by Persyarikatan Muhammadiyah which, with guidance and supervision, is given the rights and obligations to manage its own household. Ortom management at regional, regional, branch or branch level is actually the right forum for PTMA employees This is to play an active role in it. This research aims to analyze PTMA employees' understanding of the existence of Ortom in Central Kalimantan. The approach used in this research is a qualitative approach with a case study type of research. Respondent subjects for this research were PTMA employees who worked at UMPR, STIKIP Muhammadiyah Sampit and AKBID Sampit. Random sampling was used in this research. The research results show that from the indicators of understanding, the majority of respondents already understand the existence of orthoms even though they do not fully understand the massive movement of orthotoms. Active PTMA employees join Ortom Aisyiyah, Nasyiatul Aisyiyah, Pemuda Muhammadiyah and Hizbul Wathan. The recommendations of this research are : a) For PTMA leaders, create written policies in the form of circulars or decrees so that all lecturers and educational staff are actively involved in Muhammadiyah's autonomous organization; b) For the Chair of the Autonomous Organization, to massively invite the academic community to join the Muhammadiyah autonomous organization.